The Relationship between the Nutritional Status of Pregnant Women and Anemia at the Nursing Health Center in Blangkejeren City, Gayo Lues Regency, Aceh Province in 2022 - Srimis Leini Saragih (Science Midwifery, 2022)
For mothers, pregnancy is an important period in their life. During pregnancy, the mother must prepare herself to welcome the birth of her baby. A healthy mother can give birth to a healthy and physically perfect baby with sufficient body weight. Maternal nutritional status in pregnancy affects nutritional status. At the Puskesmas where the study was conducted, out of 14 pregnant women, 8 pregnant women experienced CED, as can be seen from the results of LILA measurements <23.5 cm. The purpose of this study was to determine the relationship between the nutritional status of pregnant women and the incidence of anemia at the Nursing Health Center in Blangkejeren City, Gayo Lues District, Aceh Province in 2022. The research design used was an analytical survey. The population in this study were all Trimester II and III pregnant women who came for treatment at the Nursing Center in September 2022. The sampling technique was a total population of 37 people. The research data was taken using a measuring tape and Hb Sahli. The results of this study, the nutritional status of pregnant women who were not normal were 21 respondents (56.8%), not anemic as many as 1 respondent (4.8%), anemia as many as 20 respondents (54.1%) and normal as many as 16 respondents (43.2%).), 10 respondents (27.%) were not anemic, 6 respondents (16.2%) had anemia. The results of the statistical assessment obtained a value of P = 0.000 <0.05, from the results of this study it was obtained Results There is a relationship between the nutritional status of pregnant women and anemia. In conclusion, there are many pregnant women with poor nutritional status and anemia. It is recommended that pregnant women increase their nutritional intake and consume Fe tablets, and have their pregnancy checked 4 times during pregnancy. Advice to health workers to provide counseling to pregnant women during examinations